The face of home : a new way to look at the outside of your house - Eck, Jeremiah (Newtown, CT : Taunton Press, 2006)
"In his new book The Face of Home, Jeremiah Eck, FAIA, author of Taunton's The Distinctive Home, examines these physical and emotional characteristics, explores the concepts and applications of exterior design and how they can be successfully used to enhance the experience of home and provides a fresh, new language for describing, understanding, and shaping the face of home"
Reading the face of home -- Faces of home -- Northern light -- A symphony of roofs -- Straight-faced -- Changing of face -- Light and solid -- Two-faced neighbor -- The shoebox challenge -- House in garden -- Built over time -- Breaking symmetry -- Craftsman companion -- See-through house -- Production perfect -- Two-foot cottage -- Rooms in a row -- Back to the box -- The face of housing -- Past and present -- Open to the view -- Big and beautiful -- House of many faces -- Split decision -- Featured architects.
ARC
Department of Architecture
Keywords: Architecture -- United States -- Details; Architecture, Domestic -- United States; Landscape architecture -- United States